PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU SMKN 3 ENREKANG - S, Hikma (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
The research aimed at figuring out whether the Principal’s managerial abilities had any significant impact on the performance of the Enrekang Vocational High School. The data-collection techniques used in this study are observation, documentation, and questionnaires. The sample in this study numbered 53 people. The data analysis techniques performed in the study are by using descriptive analysis, simple linear regression analysis, validity testing, fallibility testing, and hypothetical testing. The results of the study found that the Principal’s managerial abilities had a significant impact on the teacher's performance in SMK 3 Enrekang. The results of the affirmative test of the Principal’s managerial ability on teacher performance in Vocational High School 3 Enrekang have a significant value < 0.05, which means that each of these statements is valid. The results of a variable reliability test with the value of Cronbach alpha range between 0.662-0.640 which means the value is > 0.6 which means each research variable is good, The results of this study show that the value of r square is 0, 723 which explains that the Principal’s managerial abilities have a significant impact on teachers' performance in SMK 3 Enrekang by 72.3%, and the other 27.7% explained by other variables.